Inventer des « dispositifs génératifs » à la croisée de l’ethnographie et du design - Virginie Milliot; Léna Paté (Ateliers d'Anthropologie)
In the form of a dialogue, this article looks back at a collaboration between ethnography and design. As part of an ongoing study on the practices of the Vieux Marché in Brussels, Virginie Milliot and Léna organised the “Histoires de Brol” festival. They look back on how they worked at the intersection of their two disciplines to devise a hybrid method. In the collaborative process they devised, design tools follow the intrigues of the field as closely as possible, to give shape to a “generative apparatus” of collective reflection.